Occupational self-efficacy as a predictor of work engagement employees working telecommuting during the covid-19 pandemic - Rubianto, Liroy; Kembaren, Esther Muliana (University of Muhammadiyah Malang, 2023)
The impact of the Covid-19 pandemic has had a significant impact on changes in the work environment, which has shifted from traditional to digital. Many companies have started implementing remote work systems (telecommuting). The telecommuting work system cause employees to be able to adapt to new work rhythms and face all other obstacles. The impact of the pandemic presents a challenge for companies in maintaining employee engagement to survive in an uncertain environment. Therefore, this study aims to test occupational self-efficacy's predictive power on employees' work engagement who work telecommuting during the Covid-19 pandemic. This study uses a quantitative approach with simple linear regression statistical analysis. In this study, 130 participants were found as active employees who worked at least two years in companies, had experience telecommuting during the pandemic, and were located in JABODETABEK. The results of simple linear regression showed that occupational self-efficacy was significantly able to predict 43.5% of the variance of work engagement (R2= 0.435, F (1, 128) = 98.698, p < 0.001).